(untitled) (Vietnam Journal of Community Medicine, 2025)
Summary: Differentiated thyroid carcinoma in the setting of Hashimoto’s thyroiditis generates a variety of morphological, histological, and functional alterations in the thyroid gland, presenting major challenges to thyroid-conserving surgery. Evaluate the pathological characteristics that influence the decision to thyroid conserving surgery. Objective: 39 patients with thyroid cancer tumors <2 cm on a background of Hashimoto’s thyroiditis underwent lobectomy ± central lymph node dissection from May, 2023 to May 2024, in National Hospital of Endocrinology Material and methods: Retrospective descriptive study. Results: The majority of patients were middle-aged females (38.2 ± 8.9 years) with a history of chronic thyroiditis for more than three years. Anti-TPO antibodies were detected in 97.4% of the patients. Tumors greater than 1 cm were detected in 87.2% of cases, while ultrasonography revealed questionable lymph nodes in 89.7%. Only 2.6% obtained positive FNA results for metastatic lymph nodes. Lobectomy with central lymph node dissection was the main treatment approach, with 100% of cases being papillary thyroid carcinoma. Lymph node metastasis occurred in 23.5% of patients. The only postoperative complication was hoarseness, affecting 10% of patients. After 3 months, no recurrence or metastasis was detected, but only 64.1% reached the treatment goal in euthyroid status. Conclusion: Thyroid-conserving surgery for differentiated thyroid cancer on the background of Hashimoto’s thyroiditis presents several challenges but is a safe and effective treatment option in the early stages of the disease.